The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.3174/ajnr.a0501
|View full text |Cite
|
Sign up to set email alerts
|

Improved Detection of Skull Metastasis with Diffusion-Weighted MR Imaging

Abstract: BACKGROUND AND PURPOSE:Metastasis to the skull is clinically important, but routine MR imaging offers moderate sensitivity for skull-metastasis detection in our experience. We sought to determine if diffusion-weighted MR imaging (DWI) could improve the detection of skull metastasis in patients with primary carcinomas that metastasized to bone compared with conventional MR imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
39
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 12 publications
3
39
0
Order By: Relevance
“…A study by Nemeth et al reported 100% specificity for DW MRI in detecting skull metastasis [4] . It was found that DW MRI was comparable to or more sensitive than FDG-PET/ CT [5,6] .…”
Section: Discussionmentioning
confidence: 99%
“…A study by Nemeth et al reported 100% specificity for DW MRI in detecting skull metastasis [4] . It was found that DW MRI was comparable to or more sensitive than FDG-PET/ CT [5,6] .…”
Section: Discussionmentioning
confidence: 99%
“…We observed that DW-MRI had the highest sensitivity for detecting cranial bone marrow metastasis of lung cancer, whereas the sensitivity of DW-MRI for detecting cranial bone marrow metastasis of prostate cancer demonstrated the lowest value. Nemeth et al 8 showed that DW-MRI is a useful sequence for identifying focal skull metastases of breast and lung malignancies compared with conventional MRI. However, DW-MRI is insensitive for the detection of sclerotic skull metastases of prostate carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…1 DWI is helpful in detecting lytic skull metastasis of the skull base. 5 Lytic metastases are hyperintense on DWI because of the attenuated cell packing in highly malignant tumors and T2 shinethrough effect once they are typically hyperintense on T2-weighted imaging. 5 The clival abscess presented as a cystic/ necrotic mass lesion, which is atypical for a metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…5 Lytic metastases are hyperintense on DWI because of the attenuated cell packing in highly malignant tumors and T2 shinethrough effect once they are typically hyperintense on T2-weighted imaging. 5 The clival abscess presented as a cystic/ necrotic mass lesion, which is atypical for a metastasis. In addition, DWI hyperintensity in this case was due to truly restricted diffusion, because the ADC map showed low signal intensity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation